BUILDING COMPETITIVE ADVANTAGE THROUGH LEADERSHIP AND SELF INTEGRITY - Elvie Maria; Rufinus Saragih; Brilliant Handyman Manalu; Andriasan Sudarso; Lili Suryati (Ann Publisher, 2026)
ABSTRACT. Introduction. The era of Society 5.0 is an era full of competition and comprehensive in all aspects of people's lives. Therefore, everyone must equip themselves to be able to win the competition and continue to exist by building their competitive advantage. Purpose. Leadership according to the World Economic Forum 2025, is one of the main skills needed in all fields, a leader with leadership in him functions as the foundation for the success of the organization and the achievement of goals, therefore competitive advantage through leadership is very important, where a person with leadership skills Enable to effectively lead, inspire, and manage human resources. In an era of highly competitive disruption that creates great pressure to always excel and achieve, in this day and age, integrity has become something rare because people are willing to do anything to get awards and honor. Method. In the context of spiritual service, having a competitive advantage is not to boast or do something deliberately aimed at defeating others, but rather to maintain the existence and ability to provide more value to service to the people or society, so that it becomes a differentiator because it performs better than others. Results and Discussion. Christus Sacerdos Pematangsiantar Secondary Seminary School understands the importance of leadership and self-integrity, organizes seminars as a debriefing for seminarians so that in the future in their ministry they will become effective leaders and with their integrity to be an example that inspires and builds trust among the people and the community when carrying out their pastoral duties.